Systematic Literature Review: Analysis of Research Trends and Methodologies Regarding Budgeting and Financial Analysis Practices (2015–2025) - Akbar, Muhammad; Indani , Farinza Tiara (Institut Manajemen Wiyata Indonesia, 2026)
This research aims to map trends, methodologies, and theoretical foundations of studies on budgeting practices and financial analysis for the period 2015–2025 through the Systematic Literature Review (SLR) approach guided by PRISMA. Data were obtained from the Scopus database, with 423 articles initially identified. After the selection process and quality assessment, 42 high-quality articles were further analyzed. The analysis showed that quantitative approaches were dominant (57.1%), followed by qualitative (26.2%) and mixed methods (16.7%). The main focus of the research includes capital budgeting, performance-based budgeting, and financial decision-making, emphasizing capital efficiency and risk management. Bibliometric analysis identified four main conceptual clusters: capital investment and valuation, discounted cash flow methods, risk and cost of capital, and institutional budgeting practices. Geographically, the research is dominated by studies from Europe and Asia, reflecting contextual differences between developed and developing countries. The integration of financial information systems and data analytics has proven to be a source of competitive advantage, consistent with the Resource-Based View (RBV) perspective. This study confirms the relevance of Agency Theory, Contingency Theory, Resource-Based View, and Institutional Theory in explaining variations in budgeting practices and financial analysis. Technology-based financial analysis skills are recognized as core organizational competencies in the digital era. Further research is recommended to integrate digital transformation, behavioral finance, and data-driven budgeting approaches.